Clinical efficacy and safety of high-intensity focused ultrasound combined with ultrasound-guided suction curettage at different time intervals for Cesarean scar pregnancy: a retrospective study - Yan Peng; Yu Dai; Cuili Wen; Guiyuan Yu; Ping Jin (International Journal of Hyperthermia)
Objective This study aims to assess the clinical efficacy and safety of combining high-intensity focused ultrasound (HIFU) with ultrasound-guided suction curettage for the treatment of cesarean scar pregnancy (CSP) at different time intervals.Methods A total of 115 CSP patients were enrolled and divided into two groups based on the time between HIFU ablation and suction curettage. Group A (n = 50) underwent suction curettage 24-48 h after HIFU ablation, while Group B (n = 65) had suction curettage within 6 h of HIFU ablation. The study compared and analyzed the clinical characteristics, treatment success rates, and intraoperative hemorrhage during ultrasound-guided suction curettage.Results The demographic characteristics of the two groups were similar, with no statistically significant differences observed in HIFU parameters, treatment success rates, blood loss, the use of Foley catheter balloons, or hospital expenses (p > 0.05). Importantly, suction curettage performed within 6 h after HIFU ablation resulted in shorter hospitalization times compared to suction curettage performed 24-48 h after the ablation (p < 0.05).Conclusions Suction curettage within 6 h after HIFU ablation is an effective, safe, and cost-efficient treatment for patients diagnosed with CSP.